2021
DOI: 10.3832/ifor3929-014
|View full text |Cite
|
Sign up to set email alerts
|

Composted sewage sludge as an alternative substrate for forest seedlings production

Abstract: The production of forest seedlings with adequate morphological and physiological characteristics is essential for the success of plantations. Substrates and irrigation are the major factors determining seedlings' growth. Substrates made of urban and agricultural residues are a sustainable alternative to peatbased substrates. In this study, we evaluated how composted sewage sludge substrates affect the growth and gas exchange in seedlings of Cedrela fissilis Vell. Seedlings were produced under daily irrigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
1
0
5
Order By: Relevance
“…Organic compounds such as sewage sludge have a high density and consequently low overall porosity (Raviv, 2013) but we observed that the addition of structuring materials (wood chips) in the composting process made these materials suitable for creating a growth substrate. Research (Gabira et al, 2021) was conducted to create a sediment-based substrate for growing forest seedlings. They note the successful use of sediment as a component of the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Organic compounds such as sewage sludge have a high density and consequently low overall porosity (Raviv, 2013) but we observed that the addition of structuring materials (wood chips) in the composting process made these materials suitable for creating a growth substrate. Research (Gabira et al, 2021) was conducted to create a sediment-based substrate for growing forest seedlings. They note the successful use of sediment as a component of the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Según lo que se observa las tres estaciones varían muy poco en la clasificación de géneros encontrados, gracias a su cosmopolita distribución y siendo que están en una posición geográfica muy cercana, la poca variación observada en su micro diversidad puede sugerirse que es debido a características del suelo, factores ambientales, la presencia de agua o factores humanos 24 , lo que hace que muchos de ellos presenten características dominantes a estos factores Figura 1. Diversidad de hongos de la Estación 1, Aspergillus flavipes (1), Aspergillus neoflavipes( 2), Penicillium guttulosum(3), Curvularia lunata(4), Aspergillus keveii (5), Trichoderma spirale (6), Gongronella butleri (7), Aspergillus brasiliensis (8), Aspergillus neoflavipes (9), Penicillium limosum (10), Talaromyces liani (11), Cladosporium crousii (12), Aspergillus pseudonomiae( 13), Absidia sp. ( 14), Trichoderma amazonicum (15), Penicillium limosum (16), Talaromyces flavus (17), Penicillium limosum (18), Penicillium limosum (19), Humicola fuscogrisea (20).…”
Section: Identificacion De Hongos Del Bppunclassified
“…El potencial microbiano del BPP puede ser aprovechado para el desarrollo de productos a bases de micotoxinas que pueden actuar como biocontroladores de fitopatógenos en alimentos, también contribuyen en la regeneración de suelos maltratados en la que necesitan incorporarse microorganismos presentes en la materia orgánica de bosques a través de la elaboración de compost 6,7 . Adicionalmente, los hongos filamentosos pueden ser empleados en la biotecnología fúngica porque permiten fomentar la economía circular, mitigar el cambio climático y generar la producción sostenible de alimentos, combustibles, textiles, fármacos, entre otros 8 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…De autoria própria.De acordo comMathers et al (2005),Sammons e Struve (2008) ePride (2014), é possível aumentar a eficiência da irrigação aplicada por microaspersão a partir de ajustes nas estruturas dos viveiros e nos manejos praticados, a saber: 1) instalar sistemas de irrigação com maior uniformidade na distribuição de água; 2) implantar quebra-ventos no perímetro do viveiro (Figura 8); 3) agrupar as mudas de espécies com características semelhantes; 4) controlar os volumes lixiviados; 5) utilizar substratos com maior capacidade de retenção, como a turfa, a fibra de coco e o lodo de esgoto compostado ou biossólido (Figura 8) (TRIGUEIRO;GUERRINI, 2014;KRATZ et al, 2017;GABIRA et al, 2021);Gabira et al (2020b) afirmam que para proporcionar condições adequadas de aeração e disponibilidade de água às mudas, dois ou mais materiais devem ser utilizados na composição de um substrato. Nesse sentido,Simões et al (2012),Kratz e Wendling (2013);Kratz et al (2013a) eGabira et al (2020a) alertam para necessidade de se ajustar os manejos praticados no viveiro em função das características físicas e químicas dos substratos; 6) dispor as mudas nos canteiros de forma a reduzir as áreas vazias; 7) não irrigar em dias chuvosos; e 8) adotar a irrigação cíclica, isto é, dividir uniformemente o volume de irrigação diário aplicado em intervalos (ciclos).…”
unclassified